Penerapan Rekam Medis Elektronik di Rumah Sakit di Indonesia: Kajian Yuridis - Rubiyanti, Neng Sari; Suharto, Gatot (MAGISTRA Law Review, 2023)
Electronic Medical Record (RME) is a system that contains medical and disease history, diagnostic test results, information on medical expenses and other medical data. On September 12 2022, the Ministry of Health (Kemenkes) of the Republic of Indonesia issued the RME regulations contained in the Regulation of the Minister of Health or abbreviated as Permenkes No. 24 of 2022 concerning Medical Records. However, not all Health Service Facilities in Indonesia have implemented the practice of Electronic Medical Records. The Normative Juridical Method was used in this study, in which the main source of law used was Permenkes No. 24 of 2022 concerning Medical Records, Law no. 47 of 2021 concerning Hospitals and Law no. 29 of 2004 concerning Medical Practice. RME’s broad capabilities had led to its recognition as an important tool for improving patient safety and quality of care, particularly by promoting evidence-based medicine. Hospitals were also required to provide non-medical personnel in the field of information systems to support the implementation of electronic medical records in hospitals. On the other hand, the government needed to provide training so that officers and doctors in hospitals could implement RME according to the provisions of the applicable Health Regulations.